Malicious node identification routing and protection mechanism for VANET against various attack - Er. Ritika Saini; Harish Kundra (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2020)
With the help of road side unit vehicles communicate among themselves. This technique termed as VANET. This network helps us to improve the safety and efficiency of the occupants during travelling in vehicles. The basic idea of this technique is to send information about the traffic information to the road side unit or other vehicles. These vehicles get safe from attacks and misuse of their private data. The objective of this paper to secure the communication among the vehicles and the road side unit. In this technique the communication mainly dependant on the safety of the road such as vehicles tracking, emergency situations and message monitoring. There are various attacks like Sybil and Gray hole attack are vulnerable to VANET. To protect from these attacks our technique provide malicious node identification mechanism that help us to provide better facility to send data to vehicles safely. To avoid these types of attacks, our propose technique include feature like key management system to prevent the communication among the vehicles. Our proposed system mostly focus on Bandwidth, packet loss and packet delivery ratio [12].